Perspectives for a new realization of the pascal by optical methods. (6th November 2017) - Jousten, Karl; Hendricks, Jay; Barker, Daniel; Douglas, Kevin; Eckel, Steve; Egan, Patrick; Fedchak, James; Flügge, Jens; Gaiser, Christof; Olson, Douglas; Ricker, Jacob; Rubin, Tom; et al.
Abstract: Since the beginning of measurement of pressure in the 17th century, the unit of pressure has been defined by the relationship of force per unit area. The present state of optical technology now offers the possibility of using a thermodynamic definition—specifically the ideal gas law—for the realization of the pressure unit, in the vacuum regime and slightly above, with an accuracy comparable to or better than the traditional methods of force per area. The changes planned for the SI in 2018 support the application of this thermodynamic definition that is based on the ideal gas law with the necessary corrections for real-gas effects. The paper reviews the theoretical and experimental foundations of those optical methods that are considered to be most promising to realize the unit of pressure at the highest level of metrology.